Keputusan Pemilihan Strategi Manajemen Laba Pada Perusahaan Yang Mengalami Financial Distress - Setiawan, Putu Ery; Dwiana Putra, I Made Pande (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019), 2019)
This study discusses real earnings management and classification shifting along with accrual earnings management as an alternative strategy for companies that experience financial distress, and differences in choice of strategies at each stage of financial distress. This research was conducted on all manufacturing companies listed on the Stock Exchange for six years from 2012 to 2017 experiencing financial distress. The number of IDX issuer companies in the manufacturing sector that experienced financial distress in this period was 43 companies with a total of 258 observation data. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that in the early stages of financial distress companies tend to choose the strategy of real earnings management in the form of decreased production and classification shifting. While in the later stages the chosen strategy is real earnings management through a reduction in selling, general and administrative costs. Finally at the extreme stage, companies tend to make income-decreasing accruals.